Local risk management in the framework of contemporary social transformations - Guntanis, Laura Cerdas (2022)
Introduction: this article derives from the Final Graduation Project entitled Disaster Risk Management: ethical foundations and theoretical-methodological perspectives, as part of the Postgraduate Program in Social Work, with an emphasis on Research. Objective: analyze in the historical development of capitalism the main theoretical-methodological inflections and the ethical-political directionality, corresponding to the origin and consolidation of the local risk management approach, highlighting the social nature of risk, as well as the local dimension of its management. Method: the research was developed from a critical historical perspective, making use of techniques such as bibliographic and documentary review, as well as semi-structured interviews with experts, given their research and institutional experience on the subject. Results: the reconstruction of the historicity of the foundations of local risk management in the dynamics of the capitalist system, implied in the double relationship: Nature - Society and History - Theory, represented the historical - theoretical framework for the discussion around the social character of the risk, as well as the local dimension of its management in the context of contemporary social transformations. Conclusions: the genesis of the risk that populations face in local spaces places the ethical and political imperative of making inequality visible as the material basis of vulnerability. It implies, therefore, the questioning around the particularities that risk management acquires and its purposes, when considering itself as a transversal in development policies.